The Global Rise of Social Media: A Study of how Social Networking Sites influence Diffusion of Innovation - Olotu, Osahon (2012)
This paper explores the diffusion of innovation and behaviour of adopters towards the growth of social networks while understanding the role of innovative firms. The process by which innovation diffuses from its invention point to its adopter or end users can be defined as Diffusion of innovation (Robertson, 1967). The rise or growth of digital media has brought about intense competition for competitive firms in their quest for audience revenues while harnessing the potential of the internet through incremental and radical innovations. The growing literature on the contribution of innovative firms and new product development makes it unblemished that evidence about consumer behaviour on social networking platform to product innovation is a perilous input. Drawing on the present studies that explores consumer behaviour in light of motivational factors, home communication technology infrastructure, existing media use level and demographic attributes, research with digital media firms is drawn on to explore the overlapping twin logics of diffusion of innovation and behaviour of innovative firms towards product development. Over the last 60 years, researchers have studied the spread of new ideas and in thus explaining the factors in innovation processes and activities. Also, theory on the diffusion of innovations has been placed under scrutiny based on performance outcomes, adoption and diffusion patterns. The postulation underpinning this research is that, due to the recent global rise of digital media, it is however not arbitrary to take on that we might expect to see the diversity of attributes being patterned into distinct configurations. Drawing upon recent experience with internet start-ups and established internet social networking firms, the paper analyses the consumer behavioural constraints on the rapid diffusion of new innovations. Having examined processes and practices of product innovation in digital media, the article turns to some of the critical issues around firms and industry conventions towards how consumers adopt innovative product. This research stands to present a combinative methodology to the research of consumer behaviour founded on the adoption hypothesis of the innovation rather than the effects that it portrays. The task for innovative firms that this article intends to address is the ability to manage and balance the diffusion pattern of innovation, the elimination of waste of time when considering market segmentation of new products and the cultural imbalance that disrupts adoption of innovation while understanding how consumers of social media reacts to diffusion of innovation. This complex sorting of the understanding displays a stronger assessment of connection concerns between innovative firms, its consumers and the innovation.